2020
DOI: 10.5812/jkums.98429
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Eight Weeks of Aerobic Exercises on the Cardiac Function and Inflammatory Markers of Male Patients with Heart Failure After Coronary Artery Bypass Grafting

Abstract: Background: Cardiovascular diseases are the leading cause of mortality across the world. Coronary artery bypass grafting (CABG) is frequently performed on patients with cardiac diseases, the outcomes of which are closely associated with lifestyle modification, especially physical exercise. Objectives: The present study aimed to evaluate the impact of aerobic exercises on the cardiac function and inflammatory markers of male patients with heart failure after CABG. Methods: This clinical trial was conducted on 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
2
4
0
Order By: Relevance
“…While it is generally accepted that the minimum amount of time that is considered necessary for exercise to promote measurable improvements in cardiorespiratory performance is approximately 3 months ( 42 ), our exercise program length is consistent with other studies that have demonstrated 8 weeks to be sufficient to show positive changes in cardiorespiratory fitness and function ( 43 , 44 ). Our findings of an improvement in HRR in as little as 4 weeks of moderate intensity exercise are encouraging and suggest that HRR may capture cardiorespiratory improvements that are relevant for exercise-induced cognitive gains.…”
Section: Discussionsupporting
confidence: 85%
“…While it is generally accepted that the minimum amount of time that is considered necessary for exercise to promote measurable improvements in cardiorespiratory performance is approximately 3 months ( 42 ), our exercise program length is consistent with other studies that have demonstrated 8 weeks to be sufficient to show positive changes in cardiorespiratory fitness and function ( 43 , 44 ). Our findings of an improvement in HRR in as little as 4 weeks of moderate intensity exercise are encouraging and suggest that HRR may capture cardiorespiratory improvements that are relevant for exercise-induced cognitive gains.…”
Section: Discussionsupporting
confidence: 85%
“…In Iran, heart diseases are among the most important causes of death. According to the statistics of the Iranian Ministry of Health, more than 46% of deaths in Iran are due to this disease (3). Cardiac patients should be continuously cared for, and cardiac rehabilitation within the framework of regular exercise acts as an essential component of a comprehensive secondary prevention program that can reduce cardiac mortality by 25 -50% (4).…”
Section: Introductionmentioning
confidence: 99%
“…According to the statistics of the Iranian Ministry of Health, more than 46% of deaths in Iran are due to this disease (3). Cardiac patients should be continuously cared for, and cardiac rehabilitation within the framework of regular exercise acts as an essential component of a comprehensive secondary prevention program that can reduce cardiac mortality by 25 -50% (4). The rate of left ventricular ejection fraction is the most critical factor in the prognosis of patients after coronary artery bypass surgery (CABG), heart failure, especially systolic heart failure, and is an index by which the degree of failure is measured.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations